2012
DOI: 10.1007/s00421-012-2425-6
|View full text |Cite
|
Sign up to set email alerts
|

Gender effects on the coordination of subdivisions of the trapezius muscle during a repetitive box-folding task

Abstract: This study aimed at investigating gender difference in the coordination of the subdivisions of the trapezius muscle during a repetitive box-folding movement task. Twenty-two healthy volunteers (11 males and 11 females) performed the repetitive box-folding task for 34 min. During the task, perceived exertion and surface electromyographic (EMG) signals from the upper, middle, and lower trapezius subdivisions were recorded. Absolute and normalised root mean square (RMS) values as well as normalised mutual informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 36 publications
5
36
1
Order By: Relevance
“…This produced a higher FRR among females than males. Higher neck and shoulder muscle activation in females compared to males was also observed in a few previous studies (Johansen et al, 2013;Nordander et al, 2008). Lindman et al (1991) reported that females possess lower functional capacity due to a smaller cross-sectional fiber area.…”
Section: Discussionsupporting
confidence: 56%
“…This produced a higher FRR among females than males. Higher neck and shoulder muscle activation in females compared to males was also observed in a few previous studies (Johansen et al, 2013;Nordander et al, 2008). Lindman et al (1991) reported that females possess lower functional capacity due to a smaller cross-sectional fiber area.…”
Section: Discussionsupporting
confidence: 56%
“…More studies elaborating on pain mechanisms using quantitative sensory testing among computer users [53] are needed to obtain a more profound understanding of the WMSD [1]. Issues related to ergonomics, i.e., working posture and motor control were not addressed even though these are known to play a role in the gender differences found in WMSD [18,54-56]. Thus, confounding factors related to uncontrolled ergonomic, psychosocial, and personal factors cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…To create dyads for testing social coordination, the 27 first-degree relative participants and the 27 matched control participants were randomly paired with 54 unmatched healthy partners. All partner pairs were of the same sex to avoid methodological bias (Katic et al, 2012, 2013; Johansen et al, 2013). But, note that although 54 healthy partners were unmatched on the age, level education, and premorbid IQ with the relatives and controls, they were matched between them (see Table 1).…”
Section: Methodsmentioning
confidence: 99%